2013
DOI: 10.1021/jp310872a
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Benzene with Methane over ZnZSM-5 Zeolites Studied with Solid-State NMR Spectroscopy

Abstract: Alkylation of benzene with methane was studied under oxidization condition over ZnZSM-5 zeolites by using in situ solid-state NMR spectroscopy and GC-MS analysis. The experimental results indicate that the alkylation reaction occurs with selective formation of toluene at temperatures of 523–623 K using O2 or N2O as the oxidant. Using 13C isotope labeled reactants, the conversions of methane and benzene were independently monitored, and their respective role in the reaction was determined. It was found by NMR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…In addition to the activation of methane, ZnZSM-5 catalysts also show good catalytic ability for the alkylation of benzene with methane using O 2 or N 2 O as the oxidant at temperatures between 523-623 K ( Figure 18 A). [ 70 ] In situ solid-state NMR spectroscopy, 13 C isotope labeled reactants, and GC-MS analysis were used to explore the reaction process. In this reaction, methane was activated into methoxy species and zinc methyl intermediates on ZnZSM-5.…”
Section: Alkylation Of Benzenementioning
confidence: 99%
“…In addition to the activation of methane, ZnZSM-5 catalysts also show good catalytic ability for the alkylation of benzene with methane using O 2 or N 2 O as the oxidant at temperatures between 523-623 K ( Figure 18 A). [ 70 ] In situ solid-state NMR spectroscopy, 13 C isotope labeled reactants, and GC-MS analysis were used to explore the reaction process. In this reaction, methane was activated into methoxy species and zinc methyl intermediates on ZnZSM-5.…”
Section: Alkylation Of Benzenementioning
confidence: 99%
“…[1][2][3] Studies showed that hierarchical porous ZSM-5 could overcome the limitation of micropores to achieve better catalytic performance. [1][2][3] Studies showed that hierarchical porous ZSM-5 could overcome the limitation of micropores to achieve better catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aromatization of methane, other reactions such as the reaction between methane and CO 2 [67] and the one between methane and CO [68] have also been studied using SSNMR. The methane activation pathways in these scenarios help reveal the activation mechanism of methane.…”
Section: Reaction Mechanism Studymentioning
confidence: 99%